Synthesis, Characterization and Antimicrobial Properties of Some Transition Metal Complexes with NS-Chelating Schiff Base Ligand Incorporating Thiophene and Sulfonamide Moieties - Bogale Zemede, Yiheyis; Nithyakalyani, D.; Ananda Kumar, S. (Asian Journal of Chemistry, 2015)
Schiff base namely 4-[(thiophene-2-yl)methyleneamino]phenyl sulfonamide (L) and its Co(II), Ni(II), Cu(II) and Zn(II) complexes were synthesized and characterized by UV-visible, IR, 1H NMR, MS-EI, elemental analysis and TGA. Molar conductance and magnetic susceptibility of the complexes were also analyzed. Elemental analyses confirmed a 2:1 molar ratio of ligand to metal ion of the complexes. IR spectra revealed that the ligand is coordinated to the metal ions through azomethine-N and thiophene-S. On the basis of experimental data octahedral geometry was proposed for all complexes. Thermal studies together with IR showed the presence of lattice and coordinated water molecules in all complexes. The in vitro antimicrobial activities of the compounds were tested against S. aureus, K. pneumoniae, C. albicans and C. krusei by the agar well diffusion assay. The result indicated that the ligand become antimicrobially active on chelation with metal ions. It was found that Cu(II) complex showed the highest antibacterial activity among all complexes.